2015
DOI: 10.1002/2014gc005643
|View full text |Cite
|
Sign up to set email alerts
|

Early sedimentation and deformation in the Kumano forearc basin linked with Nankai accretionary prism evolution, southwest Japan

Abstract: Early forearc basin sedimentation and subsidence appear to be linked with convergent margin evolution, yet they do not follow predictable spatiotemporal patterns. In the Kumano basin of southwest Japan, 3-D seismic mapping of major unconformities, combined with biostratigraphic age constraints from two Integrated Ocean Drilling Program (IODP) drill sites illustrates the development of several tectonostratigraphic packages during early evolution and initial creation of accommodation space in the forearc basin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 55 publications
0
53
0
Order By: Relevance
“…Recently, Ramirez et al . [] pointed out for the Nankai wedge that stabilization due to the formation of the KFB could have led to deactivation of the ancient OOST underneath the KFB [ Tsuji et al ., , ; Boston et al ., ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Ramirez et al . [] pointed out for the Nankai wedge that stabilization due to the formation of the KFB could have led to deactivation of the ancient OOST underneath the KFB [ Tsuji et al ., , ; Boston et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…Reflection seismic and borehole data from accretionary margins have provided precise position and timing of internal deformation structures inside the accretionary wedges. For instance, seismic stratigraphy and borehole data from Nankai Trough, SW Japan, have revealed the existence of prominent OOST adjacent Kumano forearc basin (KFB) (referred to as the Megasplay Fault [ Park et al ., ]) and its temporal variation in fault activity [ Strasser et al ., ; Gulick et al ., ; Kimura et al ., ; Ramirez et al ., ; Boston et al ., ]. Recent attempts to reconstruct deformation history of the accretionary wedge adjacent to the KFB, using the stratigraphy of wedge‐top basins, have strongly corroborated control of sedimentation on wedge stabilization and temporal variation of the Megasplay Fault activity [ Hayman et al ., ; Moore et al ., ; Ramirez et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…3), cores from gas-hydrate exploration wells document significant accumulation of sandy turbidites in braided channels and fans with ages as old as 2.4 Ma within the slope sediment section (Noguchi et al, 2011;Takano et al, 2013). Further details of the origin and evolution of the slope sediment unit are addressed by Ramirez et al (2015), who subdivided SS into three subunits.…”
Section: Tectono-stratigraphic Units Of Kumano Forearc Basinmentioning
confidence: 99%
“…There have been significant fluctuations of sediment provenance and shifts in delivery pathways and rerouting since the basin's initiation [35][36][37][38]. A margin-wide assessment has shown that the submarine fans have transformed over time from a braided channel-dominated system to a small fan dominated system with shrinking, separated, small basins; to a trough fill turbidite system; to a channel-levee system [39][40][41]. These changes in depositional processes over time affect the spatio-temporal delivery of organic matter necessary for methane production as well as the distribution of potential reservoirs given that turbidites, ash layers, and channel fill sediments are most likely to host high concentrations of GH and free gas [42].…”
Section: Kumano Basin Evolutionmentioning
confidence: 99%
“…Gas-charged fluids are at least partially confined in stratigraphic traps under the cap of the anticlinal-shaped accreted sediments ( Figure 10) and within the intercalated synclinal-shaped sediments which corresponds to the ponded slope basins in the early stages of prism growth (Figures 4, 6 and 7) [41].…”
Section: Seismic Evidence For Gas and Gh Trapsmentioning
confidence: 99%